International Financial Reporting Standards : A Practical Guide, 5th Edition - Van Greuning, Hennie (World Bank, 2012)
The publication of this fifth edition coincides with the convergence in accounting standards that has been a feature of the international landscape since the global financial crisis of 1998. The events of that year prompted several international organizations, including the World Bank and the International Monetary Fund, to launch a cooperative initiative to strengthen the global financial architecture and to seek a longer-term solution to the lack of transparency in financial information. A conscious decision has been made to focus on the needs of executives and financial analysts in the private and public sectors who might not have a strong accounting background. This publication summarizes each standard so managers and analysts can quickly obtain a broad overview of the key issues. Detailed discussion of certain topics has been excluded to maintain the overall objective of providing a useful tool to managers and financial analysts. In addition to the short summaries, most chapters contain basic examples that emphasize the practical application of some key concepts in a particular standard. This text provides the tools to enable an executive without a technical accounting background to: (1) participate in an informed manner in discussions relating to the appropriateness or application of a particular standard in a given situation, and (2) evaluate the effect that the application of the principles of a given standard will have on the financial results and position of a division or of an entire enterprise.